Health co-benefits of climate change mitigation for the bus system of hanoi - Lien, Nguyen Thi Yen; Dung, Nghiem Trung (Vietnam Journal of Science and Technology, 2018)
The real–world driving data of the five bus routes of Hanoi, namely No. 9, 18, 25, 32 and 33, were collected using a GPS with the update rate of 1 Hz. GPS data were processed and used to simulate the emission by IVE model for the base state and three scenarios of air pollution control of Hanoi bus system. Co-benefits of climate, air quality and health were deternined. The obtained results show that either the fuel switching or the tightening of emission standards bring significant benefits of environment and health.